Rethinking the neo-corporatist framework - Breznik, Maja (Teorija in praksa, 2025)
We examine the relationship between Slovenian neo-corporatism and the welfare state, focusing on long-term care. As corporatism is a struggle against capital, but within the structures of capitalism, it is unable to resist the extension of capitalist relations to the welfare state. However, this extension was expected to have only a limited impact on the public sector, namely increasing the quality and diversity of services. Our analysis shows that a market logic has prevailed throughout the sector. This has significantly reduced the influence of trade unions on the welfare state, which they exchanged for their subordination to capital.
Keywords: commodification; corporatism; delovne migracije; dolgotrajna oskrba; Javni sektor; korporativizem; labour migration; long-term care; poblagovljenje; Slovenia; Slovenija; social spending; socialna država; socialni izdatki; Socialno skrbstvo; welfare state